Preferential Subgenome Elimination and Chromosomal Structural Changes Occurring in Newly Formed Tetraploid Wheat—Aegilops ventricosa Amphiploid (AABBDvDvNvNv) - Zhang, Jie; Yang, Fan; Jiang, Yun; Guo, Yuanlin; Wang, Ying; Zhu, XinGuo; Li, Jun; Wan, Hongshen; Wang, Qin; Deng, Ziyuan; Xuan, Pu; Yang, WuYun (Frontiers in Genetics, 2020)
Artificial allopolyploids derived from the genera Triticum and Aegilops have been used as genetic resources for wheat improvement and are a classic example for evolution via allopolyploidization. In this study, we investigated chromosomes and subgenome transmission behavior in the newly formed allopolyploid of wheat group via muti-color Fluorescence in situ hybridization (mc-FISH) using pSc119.2, pTa535, and (GAA)7 as probe combinations, to enabled us to precisely identify individual chromosomes in 381 S3 and S4 generations plants derived from reciprocal crosses between Ae. ventricosa (DvDvNvNv) and T. turgidum (AABB). A higher rate of aneuploidy, constituting 66.04–86.41% individuals, was observed in these two early generations. Of the four constituent subgenomes, Dv showed the highest frequency of elimination, followed by Nv and B, while A was the most stable. In addition, structural chromosomal changes occurred ubiquitously in the selfed progenies of allopolyploids. Among the constituent subgenomes, B showed the highest number of aberrations. In terms of chromosomal dynamics, there was no significant association between the chromosomal behavior model and the cytoplasm, with the exception of chromosomal loss in the Dv subgenome. The chromosome loss frequency in the Dv subgenome was significantly higher in the T. turgidum×Ae. Ventricosa cross. than in the Ae. ventricosa × T. turgidum cross. This result indicates that although the D subgenome showed great instability, allopolyploids containing D subgenome could probably be maintained after a certain hybridization in which the D subgenome donor was used as the maternal parent at its onset stage. Our findings provide valuable information pertaining to the behavior patterns of subgenomes during allopolyploidization. Moreover, the allopolyploids developed here could be used as potential resources for the genetic improvement of wheat.